PERBANDINGAN PENGGUNAAN ANTIPSIKOTIK ATIPIKAL TUNGGAL DAN KOMBINASI TERHADAP KADAR GLUKOSA DARAH PADA PASIEN SKIZOFRENIA - POPI LATIFAH BAWEAN; ISRA THRISTY (LP2MTBM MAKARIOZ, 2023)
Schizophrenia is a severe mental disorder characterized by many disturbances in thinking, language, perception, and a sense of self-awareness. Pharmacotherapy in schizophrenic patients is the use of antipsychotics, either alone or in combination. In addition, antipsychotic drugs can be combined with other drugs such as antidepressants, antiparkinsonian. Concurrent administration of first-generation (typical) and second-generation (atypical) antipsychotics occurs when the administration of first/second generation antipsychotics has no effect. In the long term use of the drug can cause extrapyramidal symptoms, metabolic disorders such as increased blood glucose levels. To compare the use of single and combined atypical antipsychotics on blood glucose levels in schizophrenic patients.This research is a descriptive analytic study with a non-probability sampling technique that is carried out by taking venous blood, and then examining the blood in the laboratory using spectrophotometry. The number of samples used was 30 schizophrenic patients, of which 15 were taking a single antipsychotic drug, and 15 people taking a combination antipsychotic drug. Then the analysis was carried out using the Mann-Whitney test. The results of the Mann-Whitney test showed that there was a significant difference between the use of single antipsychotics and combination antipsychotics in schizophrenic patients with P value = 0.001 (p < 0.05). The use of combination antipsychotics has a higher risk than single antipsychotics.The use of single antipsychotics has a significant difference with combination antipsychotics on blood glucose levels in schizophrenic patients. Keywords: Schizophrenia, Antipsychotic Side Effects, Blood Glucose Level, Clozapine and Risperidone.